2016
DOI: 10.1016/j.ejogrb.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Twin pregnancies after assisted reproductive technologies: the role of maternal age on pregnancy outcome

Abstract: Our data indicate that nulliparous twin pregnancies conceived with ART in mothers ≥40 years old did not show significantly higher incidence of PB, even if an increased rate of iatrogenic PB <37 weeks is showed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
1
6
0
1
Order By: Relevance
“…We found that the relationship of maternal age with the risk of preterm birth in twin pregnancies was different than in singletons and was highest among the lowest maternal age group. While several studies on this topic found no association between maternal age and preterm birth, most of these studies did not focus on women aged less than 20 years 22,26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the relationship of maternal age with the risk of preterm birth in twin pregnancies was different than in singletons and was highest among the lowest maternal age group. While several studies on this topic found no association between maternal age and preterm birth, most of these studies did not focus on women aged less than 20 years 22,26 …”
Section: Discussionmentioning
confidence: 99%
“…The main strengths of our study are its population-based nature and large sample size, which allowed us to stratify maternal age into seven age groups rather than considering it as a dichotomous variable as in many previous studies on this topic. 2,21,22,25,26 Moreover, in contrast to prior studies, 3,21,22,25,26 we included a control group of singleton pregnancies, which allowed us to compare directly the association between AMA and pregnancy outcomes in twins with that observed in singletons. Another important strength is the availability of data on relevant confounding variables such as maternal BMI, maternal income group, race, smoking, and ART.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…Okby et al found that in IVF twin pregnancies with preeclampsia, mothers were older and had higher primipara than in twin pregnancies with preeclampsia conceived without ART [ 15 ]. Serena et al found that advanced maternal age (≥40 years) is among the risk factors for twin pregnancies with gestational hypertension/preeclampsia [ 23 ]. Our results are similar to those of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…A report published in 2018 stated that younger women were more likely to become pregnant with predominantly MD twins than older women [ 30 , 31 ]. In our present study, we also found that mothers younger than 25 years had a higher rate of delivering twins with high weight differences and were also more prone to preterm delivery.…”
Section: Discussionmentioning
confidence: 99%